Class II division 1 malocclusion treated by a modified fixed functional appliance in an adolescent boy - Vivek Agarwal; Debapratim Jana; Sathesh Kumar Sivalingam; Shirish Goel (Wolters Kluwer Medknow Publications, 2018)
Treating a Class II patient has always been a challenge to orthodontist, especially in noncompliant adolescents. An appliance that minimizes the dependence on patient cooperation, reduces the treatment duration, and is esthetically less visible offers a potential solution to some compliance problems encountered in orthodontic practice. This article presents a case report of a 13-year-old male with a Class II division 1 malocclusion treated with a modified Churro jumper, by inserting it on an auxiliary wire (consisting of a molar segment, a posterior vertical segment, a vestibular segment, and an anterior vertical segment) placed on the mandibular arch, instead of directly placing on the main arch wire, to improve its efficiency. The patient responded well to the fixed functional appliance and saved the treatment time spent in aligning the bicuspids later.